A Mathematical Model for the Routing Optimization Problem with Time Window. Issue 1 (1st April 2022) - Cheng, R; Lu, X; Yu, X
Abstract: This paper establishes a mathematical model for the routing optimization problem. Then, the model is solved by a genetic algorithm. Finally, to verify the proposed method, a case study is carried out. According to the results, the proposed model and algorithm can be used to solve the problem and obtain the optimal vehicle route with minimum time cost and travel distance.